Transgenics, agroindustry and food sovereignty - León Vega, Xavier Alejandro (2014)
Food sovereignty has been implemented constitutionally in Ecuador; however, many of the actions and policies are designed to benefit the dominant model of food production, based in agroindustry, intensive monocultures, agrochemicals and transgenics. This article reflects upon the role of family farming as a generator of food sovereignty, and secondly the threat to them by agroindustry agriculture based in transgenic. The role played by food aid in the introduction of transgenic in Latin America and other regions of the world is also analyzed.